The importance of intraoperative echocardiography in the early detection of mitral regurgitation as a postsurgical sequel of aortic valve replacement: a case report - Mehrdad Jafari Fesharaki; Tooba Akbari; Fariba Bayat; Erfan Ghadirzadeh; Elham Charkazi (Journal of Medical Case Reports, 2023)
Abstract Background Mitral leaflet perforation (MLP) can rarely be a consequence of aortic valve replacement (AVR), resulting in mitral regurgitation (MR). Determining the cause and severity of MLP following AVR is crucial in preventing hemodynamic consequences, such as pulmonary hypertension and biventricular remodeling. However, the diagnosis of this rare complication requires detailed echocardiographic evaluations. Case presentation In this paper, we report a 37-year-old Persian male with progressive dyspnea on exertion diagnosed with severe MR caused by anterior MLP following AVR and discuss the importance of intraoperative transesophageal echocardiography (TEE) in the proper and on-time diagnosis of this rare complication. Conclusion During AVR procedure, an evaluation with TEE could be beneficial for identifying and treating such condition. Echocardiography is beneficial in providing real-time guidance during surgery, early detection of potential complications, treatment of such complications if present, and prevention of adverse outcomes.